Marcos Covelo : painting (with) without paint - López López, Marta (2019)
This article presents a series of installations and creation methodology carried out by the young Spanish artist Marcos Covelo. In particular, his interest in Painting in the expanded field arises primarily in developing its Master’s Thesis from the hand of the artist Nono Bandera and Almudena Fernández Fariña. The latter is the author of the doctoral thesis’ What the painting is not. The logic of denial like affirmation of the expanded field of Painting’. So, it is a good example of how a doctoral thesis can be a source of motivation applicable in artistic practice